Non-pharmacological measures in the pain management in newborns: nursing care - Ana Paula da Silva Moraes; Silvania Moreira de Abreu Façanha; Sarah Nogueira Rabelo; Ana Valeska Siebra e Silva; Maria Veraci Oliveira Queiroz; Edna Maria Camelo Chaves (Rev Rene)
Objective: to analyze the evidence of the literature about pain management during arterial puncture, venous and capillary in the newborn that received non-pharmacological measures before the painful procedure.Methods: this is an integrative review performed in databases. Initially, 120 articles were selected being a sample composed of ten articles. Data were collected in forms. Results: orally glucose was the most used method followed by breast milk and contact measures and the use of glucose associated or not to breast milk and contact measures. Conclusion: the use of non-pharmacological methods has been proven effective to promote the relief of pain in newborns.